Optimization of Drilling of Carbon Fiber Reinforced Polymer with the Grey-Based Method - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2020)
The present study investigates the effect of cutting speed, feed rate, and drill diameter on thrust force, delamination factor, surface quality, and drill wear in drilling carbon fiber reinforced polymer composite (CFRP). The drilling tests are conducted with solid carbide drills cutting tools. In order to determine the optimum cutting conditions, the Taguchi method is used in the experimental design. The Grey relational analysis is used to optimize the drilling parameters of these composites. To minimize the compressive forces that occur during drilling, as a result of the Grey relational analysis, 0.075 feed, 4 mm drill diameter, and 50 mm/min cutting speed parameters appear to be efficient.
Keywords: MINIMUM QUANTITY LUBRICATION; STAINLESS-STEEL; MACHINABILITY; PARAMETERS; DESIGN; COMPOSITES